2003
DOI: 10.1242/dev.00872
|View full text |Cite
|
Sign up to set email alerts
|

Mitf expression is sufficient to direct differentiation of medaka blastula derived stem cells to melanocytes

Abstract: Embryonic stem (ES) cell lines have provided very useful models to analyse differentiation processes. We present here the development of a differentiation system using ES-like cell lines from medaka. These cells were transfected with the melanocyte specific isoform of the microphtalmia-related transcription factor (Mitf). Mitf is a basic helix-loop-helix-leucine zipper transcription factor whose M isoform is restricted to neural crest derived melanocytes and is essential for the development of these cells in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 46 publications
(54 reference statements)
3
86
0
1
Order By: Relevance
“…In fish, a differentiation system has been developed from the medaka MES cell line. Cells transfected with the melanocyte-specific isoform of the microphthalmia transcription factor (MITF) responded by development of appropriate pigmentation, morphology, melanosome motility, and gene expression patterns of completely differentiated pigment cells (Figure 5A and B;Bé jar et al, 2003). This work demonstrated that Mitf expression is sufficient for the proper differentiation of medaka pluripotent stem cells into melanocytes and that MES cells represent a suitable differentiation model, in which contrary to mouse, the formation of embryoid bodies is not necessary.…”
Section: Current Applications Of Fish Es Cellsmentioning
confidence: 77%
“…In fish, a differentiation system has been developed from the medaka MES cell line. Cells transfected with the melanocyte-specific isoform of the microphthalmia transcription factor (MITF) responded by development of appropriate pigmentation, morphology, melanosome motility, and gene expression patterns of completely differentiated pigment cells (Figure 5A and B;Bé jar et al, 2003). This work demonstrated that Mitf expression is sufficient for the proper differentiation of medaka pluripotent stem cells into melanocytes and that MES cells represent a suitable differentiation model, in which contrary to mouse, the formation of embryoid bodies is not necessary.…”
Section: Current Applications Of Fish Es Cellsmentioning
confidence: 77%
“…5 Similarly, ectopic expression of MITF into Medaka embryonic stem cells drives differentiation into melanocytes. 6 Conversely loss of function mutations in MITF produce depigmentation that is different from albinism, 7 where melanocytes exist but pigment production is defective. Instead, MITF deficiency produces depigmentation due to absence of viable melanocytes.…”
Section: Dual Roles Of Lineage Restricted Transcription Factorsmentioning
confidence: 99%
“…One of these lines, MES1, has been characterized as being pluripotent in vitro and in vivo. In vitro, MES1 is capable of spontaneous differentiation into various functional cell types [9] and of directed differentiation into pigment cells [11]. In MES1 cells, the totipotency-specific mouse Oct4 promoter is active [12].…”
Section: Introductionmentioning
confidence: 99%